PENGARUH PEMBERIAN EDUKASI PENCEGAHAN KEPUTIHAN MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN REMAJA PUTRI DI SMK NU MIFTAHUL FALAH KUDUS - Zulfa Laila Khoirun Nisa; Dwi Astuti; Nasriyah, Nasriyah (Yayasan Nusantara Hasana Berdikari, 2025)
Leucorrhea is a reproductive health problem frequently experienced by adolescent girls and may lead to complications if not prevented early. The lack of knowledge regarding leucorrhea prevention highlights the importance of health education using engaging methods, one of which is audiovisual media. This study aimed to analyze the effect of leucorrhea prevention education using audiovisual media on the knowledge of adolescent girls at SMK NU Miftahul Falah Kudus. This was a pre-experimental study with a one-group pretest–posttest design. The sample consisted of 60 respondents selected through purposive sampling. The research instrument was a knowledge questionnaire that had been tested for validity and reliability. Data were analyzed using a paired t-test. The results showed a significant difference with a p-value < 0.001. Education using audiovisual media is effective in improving adolescent girls’ knowledge about leucorrhea prevention. This medium can be recommended as an alternative in reproductive health promotion programs in schools.